Thulium Laser versus Staplers for Anatomic Pulmonary Resections with Incomplete Fissures: Negative Results of a Randomized Trial. Issue 3 (May 2014) - Scanagatta, Paolo; Furia, Simone; Billè, Andrea; Duranti, Leonardo; Girelli, Lara; Tavecchio, Luca Domenico; Leo, Francesco; Giovannetti, Riccardo; Pelosi, Giuseppe; Porcu, Luca; Pastorino, Ugo
Aims: This randomized trial evaluated the feasibility and safety of thulium 2010-nm laser to perform anatomic lung resections in patients with incomplete fissures, as compared to mechanical staplers with or without sealants. Study Design: Seventy-two patients scheduled for segmentectomy or lobectomy were enrolled. After intraoperative confirmation of the extent of resection and incomplete fissures (Craig type 2, 3 or 4), they were randomized and allocated to one of the following arms: laser resection by thulium (group A) or standard resection with mechanical staplers with or without sealants (group B). The primary endpoints of the study included analysis of intraoperative and postoperative course, and costs. Results: Thirty-eight patients were assigned to group A (32 lobectomies, 6 segmentectomies) and 34 to group B (31 lobectomies, 3 segmentectomies). No 30-day mortality was observed. Median operative times were 145.0 minutes (group A) and 142.5 minutes (group B, P = 0.83). The median time to drainage removal was 5 days (group A) and 4 days (group B), while the median length of hospital stay was the same (7 days). Prolonged air leaks >7 days were observed in 12 patients of group A (32%) and 10 patients of group B (29%, P = 0.46). Unpredictable late pneumothorax occurred in 3 patients of group A (2 readmissions, need for 1 repeat thoracotomy). Cost analysis demonstrated an intraoperative advantage for group A (mean 807 ± 212 euro) versus group B (mean 1, 047+/-276 euro, P <0.0001), but the differences in total costs could be due to chance (P = 0.83). Conclusions: The use of laser to complete fissures can lead to late pneumothorax, even in the absence of postoperative air leaks. Moreover, the use of laser to complete fissures did not prove to reduce overall costs. Trial Registration Identification Number: 41/10 (IRB00001457 – FWA00001798 – IORG0001063).